Pemodelan Basement Daerah Panas Bumi Non Vulkanik Lainea Konawe Selatan Berdasarkan Data Anomali Medan Gravitasi - Wahyudhy; Jamhir Safani; Al Rubaiyn (Program Studi Teknik Geofisika FITK UHO, 2023)
Basement rocks often consist of relatively older, denser, and different-density rocks compared to the overlying rock layers. These density variations create gravity anomalies that can be observed and analyzed using gravity methods. Basement modeling implementation can be utilized for geothermal exploration. In the Lainea , Southeast Sulawesi, there is geothermal potential. While some research has been conducted, no studies on basement modeling have been found. Therefore, to enrich the study, this research performs 3D basement modeling in the Lainea area based on gravity measurement data. The modeling is carried out using the Grav_D_Inv inversion program, utilizing residual gravity anomalies from complete Bouguer anomalies. The program runs on MATLAB with a graphical user interface (GUI) and relies on several parameters, including anomaly depth estimation, area size, wavenumber range for low-pass filters, density contrast, and windowing. The inverted basement in the Lainea geothermal area, integrated with geological and previous geophysical studies, can be interpreted as metamorphic rocks with intrusive igneous rocks in the central area. The Lainea geothermal basement relief tends to follow surface structural and topographic patterns, displaying intrusive structures at depths of 1200 - 1500 meters with a peak area in the southeast region of the research area.